Pemilihan Lokasi TPA Regional untuk Kota Medan dan Kabupaten Deli Serdang - Muhammad David Hablum; Ahmad Perwira Mulia; Gina Cynthia R Hasibuan (Syntax Corporation Indonesia, 2024)
The increase in the rate of development, population growth, and socio-economic activities has triggered an increase in waste generation, which is increasingly complex with conventional waste management that relies on collection, transportation, and disposal. This study aims to find a solution through three main stages: identification of waste conditions, preparation of a decision support system using the AHP Method, and analysis of the area with GIS application. The results of the study show that Limau Mungkur Village, STIM Hilir District, is considered the most appropriate location in the study area. Based on these results, the concept of selecting the criteria of Land Use, Hydrology, Groundwater Level Depth, Flood-prone Area, Settlement Distance, Zone Slope, Geology and Airport Distance became a determinant in the selection of location alternatives.